ĐẶC ĐIỂM ĐỊA CHẤT CÔNG TRÌNH NỀN ĐÊ SÔNG HỒNG KHU VỰC HÀ NỘI VÀ CÁC TAI BIẾN ĐỊA CHẤT LIÊN QUAN - Tư, Trần Văn; Đức, Đào Minh; Lan, Trần Linh (Vietnam Journal of Earth Sciences, 2012)
Geological engineering characteristic of Red River dyke basement in Hanoi and concerning geological hazards Series of problems of infiltration and seepage deformation, as well as slope failure of river band and dike of Red River in Hanoi has made the administators and people to be fearful. In history, dike breaks have occurred in many places, influencing on the social-economic situation of the region. The major cause of the above geological hazards is engineering geological conditions of the dyke foundation. This paper presents analysis on the formation and geological engineering properties of the Quaternary sediment near Red River, especially dyke foundation in Hanoi. Simultaneously, the paper have marked out some of the geological hazards such as infiltration, seepage deformation in the flood, dyke slope slide, settle of the dyke surface and the cracks extend from dyke to the river bank. These information are useful to the administrator to defend dyke in flood season.